The Influence of Overconfidence on Students' Investment Decisions in the Stock Market: The Moderating Role of Financial Literacy - Anisyah Eka Mandiri; Sriwidharmanely Sriwidharmanely (Transpublika Publisher, 2025)
This study aims to examine the influence of overconfidence on students' investment decisions in the capital market by considering the moderating role of financial literacy. Overconfidence is a psychological bias in which individuals have excessive confidence in their knowledge and abilities when making investment decisions. This study uses a quantitative approach involving the younger generation, especially students who have or are investing in the capital market. Researchers collected a sample of 378 respondents through a questionnaire distributed using Google Forms. Researchers then analyzed the data using the PLS-SEM method. The results of the study show that overconfidence has a negative impact on investment decisions. The higher the level of overconfidence, the worse the decisions taken by individuals. Conversely, financial literacy has a positive impact by helping individuals make more rational investment decisions. In addition, financial literacy also acts as a moderator that can reduce the negative impact of overconfidence, thereby improving the quality of investment decision making. These findings confirm that financial literacy has an important role in reducing the negative impact of overconfidence and encouraging individuals to make wiser investment decisions.